The Utilization of Gadgets in Arabic Language Learning for Early Childhood through a Fun-Based Learning Approach - Setiadi, Fadlan Masykura; Khairunnisa, Khairunnisa (Seulanga : Jurnal Pendidikan Anak, 2025)
This study explores how gadgets can enhance Arabic learning through a fun-based learning approach at TK Az-Zalfa Mandailing Natal. This study employed a descriptive qualitative method, data were collected through participatory observation, semi-structured interviews with teachers and the school principal, and documentation of classroom activities, involving three teachers, one principal, and nine children aged 5–6 years. Data analysis was conducted through data reduction, thematic categorization, and triangulation. The findings showed that the utilization of gadgets has been effectively integrated into learning sessions using applications such as Marbel Bahasa Arab, Memrise, and YouTube Kids, which supported vocabulary acquisition, listening practice, and verbal participation while fostering contextualized and enjoyable learning experiences. Other results also showed high attention focus (M = 4.2), fairly high verbal participation (M = 3.8), very high play enthusiasm (M= 4.6), and moderate independence in gadget use (M = 3.5). This study contributes to the literature on foreign language learning in early childhood by emphasizing the potential of fun-based digital strategies in Islamic education, highlighting the critical role of teachers as facilitators in balancing technology use with developmental needs, and providing practical implications for educators and curriculum developers in designing innovative, adaptive, and inclusive Arabic learning models.